The Occurrence of Cynoglossus macrolepidotus (Bleeker, 1851) and Cynoglossus arel (Bloch & Schneider, 1801) Along the Mumbai Coast, India - Sharma , Shravan Kumar; Jaiswar , A. K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
The results of the morphometric, meristic, and osteological study, including scale, otoliths, and radiographs for distinguishing Cynoglossus arel (Bloch & Schneider, 1801) and C. macrolepidotus (Bleeker, 1851) presented here. A total of 72 specimens of C. arel and 37 specimens of C. macrolepidotus collected from the Indian coast (Mumbai, Ratnagiri, and Veraval) from August 2013 to May 2014. It was found that the shape, structure of otoliths; vertebrae number species through radiographs; type, shape, and ctenii structure and number are the primary tool for taxonomy and used for species discrimination. In this study, two species C. arel and C. macrolepidotus, are discriminated based on their morphological and osteological characters. It proved that C. macrolepidotus is a valid species, and also found in the west coast of India along with C. arel.